PENERAPAN METODE RESITASI BERWAWASAN LINGKUNGAN DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KOMPETENSI BELAJAR FISIKA SISWA SMP NEGERI 2 PADANG - Yusmaridi, Yusmaridi; Ratnawulan, Ratnawulan; Fauzi, Ahmad (Universitas Negeri Padang, 2012)
VIII.1 graders SMPN 2 Padang is the students who have high academic ability. However, there are some problems such as teachers' learning is not maximized in the delivery of the task, teachers are less able to interpret the potential of students, teachers dominate lessons. The impact of the fact that low mastery of concepts and affective competencies of students. The research objective is to improve the mastery of concepts and develop affective competencies students of SMPN 2 Padang through the application of environmentally sound methods of recitation in cooperative learning and to know the student responses to learning activities undertaken. type of research is action research class. Subjects were students VIII.1 class of SMPN 2 Padang totaling 31 people. Action research conducted in two cycles. I covered the action planning cycle, action, observation, and reflection Action cycle II is a follow-up and modification of cycle I. Success criteria is the concept of achieving mastery KKM set is 80 and the percentage increase in affective competencies are in good criterion (61% -80%). The research data were collected through the mastery of the concept of the test results, observation sheets affective competencies, field notes, students' suggestions critique sheet, photographs and video recordings. Data analysis is a technique percentage.The results are described based on the data acquisition and mastery of the concept of affective competencies of data per cycle. The average value of the concept of mastery increased from 72.8 to 89.3 in cycle I to cycle II in other words, the cycle I is not complete KKM to complete the second cycle. Increased mastery of the concept is also accompanied by an increase of 53.6% affective competency in cycle I to 82.8% in the second cycle of the criteria in other words Enough (C) on a cycle I became very good (A) in the second cycle. Conclusions of research is the application of environmentally sound methods of recitation in cooperative learning can enhance the mastery of concepts and competencies in the affective student learning in physics VIII.1 class students of SMPN 2 Padang.